2010
DOI: 10.1111/j.1445-2197.2009.05108.x
|View full text |Cite
|
Sign up to set email alerts
|

Missed lesions in synchronous multiple gastric cancer

Abstract: Preoperative gastroscopy should be performed meticulously in the entire stomach, especially in older men, in order to identify the presence and locations of cancer lesions that might otherwise be missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, most missed lesions were gross type IIa‐c. These results are consistent with those of recent studies by Ha et al 23 and Lee et al 24, who demonstrated that the risk factors for missed lesions were small size, middle‐third location and flat type.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, most missed lesions were gross type IIa‐c. These results are consistent with those of recent studies by Ha et al 23 and Lee et al 24, who demonstrated that the risk factors for missed lesions were small size, middle‐third location and flat type.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies of missed lesions have been conducted, and only the proportion of missed lesions has been reported. In studies published in the 1980s and 1990s, the proportion of missed lesions was 23–52%, and decreased to 12–20% in recent studies due to the development of new endoscopic instruments and techniques 6–8, 23, 24. In this study, not only the incidence of missed lesions, but also characteristics of missed lesions were analyzed.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, EGD is highly accurate for the diagnosis of upper GI diseases; however, due to the high prevalence of upper GI malignancy in Asian countries and in light of the results of previously published reports, missed lesions, even cancers, are not as rare as we expect . Some patients with FD will doubt the accuracy of the initial diagnosis if the dyspeptic symptoms persist or recur after medical treatment, and a small proportion of such patients ask for a re‐examination.…”
Section: Discussionmentioning
confidence: 84%
“…Overall, EGD is highly accurate for the diagnosis of upper GI diseases; however, due to the high prevalence of upper GI malignancy in Asian countries 17 and in light of the results of previously published reports, missed lesions, even cancers, are not as rare as we expect. 8,18,19 Some patients with FD will doubt the accuracy of the initial diagnosis if the dyspeptic symptoms persist or recur after medical treatment, and a small proportion of such patients ask for a re-examination. Japanese authors reported a rate of missed upper GI malignancies after endoscopy of 7.2% within 3 years after a normal endoscopy; 20 while Raftopoulos et al 8 found the rate of missed upper GI malignancy at 1 and 3 years to be 1.1% and 2.1% for Australian patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple tumors may exist in the chronic inflammatory background mucosa and synchronous tumors may not be detected. According to previous reports, the incidence of synchronous multiple gastric cancer is more common (3.2–12.3%) in early gastric cancer patients [ 11 , 12 , 13 , 14 , 15 ] than in those with advanced gastric cancer [ 16 , 17 ]. Endoscopists need to pay attention to novel methods to easily detect multiple synchronous lesions; however, such methods have not been clearly established yet.…”
Section: Introductionmentioning
confidence: 99%